PEMBERIAN KOMPRES KENTANG TERHADAP MASTITIS NON INFEKSI PADA IBU MENYUSUI - Riris Sitorus; Grace Erlyn Damayanti` S; Diah Evawanna Anuhgerah; Nikmah Jalilah Ritonga; Raisha Octavariny (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2021)
the baby and affects the biological health of both mother and baby. However, the breastfeeding process could be hampered due to problems, one of which was mastitis. Mastitis occured due to the narrowing of the lactiferous ducts in the breast and the mother may have flat, sunken or immersed nipples. So that the breasts become swollen, painful when pressed so that the mother feels breast discomfort. The impact of mastitis greatly affected the health of both mother and baby. The mother would felt pain during breastfeeding so that she could experience high fever. Whereas in infants the need for breast milk was not optimal from the content of the milk. One of the efforts that could be done to overcome the occurrence of mastitis in nursing mothers was by applying a potato compress. This study aimed to determined the effect of potato compresses on non-infectious mastitis in nursing mothers. The research method used was pre-experiment (quasi-experimental) using the one group pre-test-post test technique. The population of this study were breastfeeding mothers with non-infectious mastitis with a sample size of 10 people with a purposive sampling technique. The results showed that using the Paired Sample T-Test analysis test obtained a p-value of 0.000 <Î± = 0.05, it can be concluded that there was an effect of Potato Compress on Non-Infectious Mastitis in Breastfeeding Mothers. It is recommended that health workers provide information for breastfeeding mothers about potato compresses to treat non-infectious mastitis. Keywords: Potato compress; non-infectious mastitis.